Henryk Jakubanis (1879-1949) - historyk filozofii greckiej między Kijowem i Lublinem - Sargsyan, Mariam (Lublin: Towarzystwo Naukowe Katolickiego Uniwersytetu Lubelskiego)
Henryk Jakubanis (1879-1949) was a researcher of antiquity and a historian of ancient philosophy. He was born in central Russia to a Polish family of Lithuanian origin. The intellectual biography of this researcher is usually divided into two periods: Kyiv (1897-1922) and Lublin (1922-1949). The Lublin period is quite well studied by Polish authors, while the importance of the Kyiv period can be assessed on the basis of the preserved archival materials, which are in the University Library of the Catholic University of Lublin, and the works of Jakubanis published in Kyiv.
Keywords: Jakubanis, Henryk (1879-1949); filozofia polska - historia; Kijowski Uniwersytet św. Włodzimierza; Katolicki Uniwersytet Lubelski; history of Polish philosophy; Saint Vladimir Imperial University of Kyiv; Catholic University of Lublin